The Cambridge Bible for schools and colleges - Perowne, J. J. Stewart (Bible., 1884)
[1] Introduction to the Pentateuch,.--[2] Genesis, ed. by .--[3] Exodus, ed. by .--[4] Leviticus, ed. by .--[5] Numbers, ed. by .--[6] Deuteronomy, ed. by .--[7] Joshua, ed. by G. F. Maclear. 1899.--[8] Judges, ed. by J. J. Lias. 1902.--[9] Ruth, ed. by [10-11] Samuel, ed. by A. F. Kirkpatrick. 1890-91.--[12-13] Kings, ed. by .--[14] Chronicles, ed. by .-- [15] Ezra and Nehemiah, ed. by .--[16] Esther, ed. by .--[17] Job, ed. by A. B. Davidson. 1891.--[18-20] Psalms, ed. by A. F. Kirkpatrick. 1891.-- [21] Proverbs, ed. by .--[22] Ecclesiastes, ed. by [23] Song of Solomon, ed. by [24-25] Isaiah, ed. by .--[26] Jeremiah and Lamentations, ed. by A. W. Streane. 1891.--[27] Ezekiel, ed. by A. B. Davidson. 1906.--[28] Daniel, ed. by [29] Hosea, ed. by T. K. Cheyne. 1899.--[30] Joel and Amos, ed. by .--[31] Obadiah and Jonah, ed. by T. T. Perowne. 1905.--[32] Micah, ed. by .--[33] Nahum, Habakkuk and Zephaniah, ed. by .--[34] Haggai and Zechariah, ed. by .--[35] Wisdom of Solomon, ed. by .--[36] Ecclesiasticus, ed. by .- -[37] I Maccabees, ed. by .--[38] St. Matthew, ed. by A. Carr. 1894.--[39] St. Mark, ed. by G. F. Maclear. 1893.--[40] St. Luke, ed. by F. W. Farrar. 1895.--[41] St. John, ed. by A. Plummer. 1884.--[42] Acts of the Apostles, ed. by J. R. Lumby. 1893.--[43] Romans, ed. by H. C. G. Moule. 1889.--[44- 45] Corinthians, ed. by J. J. Lias. 1896-97.--[46] Galatians, ed. by E. H. Perowne. 1896.--[47] Ephesians, ed. by H. C. G. Moule. 1895.--[48] Epistles to the Philippians, ed. by H. C. G. Moule. 1889.--[49] Colossians and Philemon, ed. by H. C. G. Moule. 1893.--[50] Epistles to the Thessalonians, ed. by G. G. Findlay. 1898.--[51] Epistles to Timothy and Titus, ed. by A. E. Humphreys. 1897.--[52] Epistle to the Hebrews, ed. by F. W. Farrar. 1893.--[53] Epistle to St. James, ed. by E. H. Plumptre. 1895.--[54] Epistles of St. Peter and St. Jude, ed. by E. H. Plumptre. 1897.--[55] Epistles of St. John, ed. by A. Plummer. 1896.--[56] Revelation, ed. by W. H. Simcox. 1898.